2009
DOI: 10.1007/s10608-009-9279-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Biases in Depression and Eating Disorders

Abstract: This study examined the link between cognitive biases (i.e., attention biases and implicit associations) and symptoms of depression and eating disorders and whether the content of these biases is disorder-specific. These hypotheses were examined with a sample of 202 undergraduate women. Cognitive biases were measured via computer-based tasks (i.e., the probe detection task and the Implicit Association Test) and symptom levels were measured via interview and self-report. Partially supporting the main hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…While past self-report studies generally show an inverse association between selfesteem and symptom severity, findings from studies using neurocognitive tasks, specifically an implicit association task which paired self-related words with positive and negative words, are mixed. For example, one study, in undergraduate women, found that negative self-evaluation negatively predicted eating disorder severity (Benas & Gibb, 2011), while a second, in patients with and without an eating disorder, found that only explicit, but not implicit, self-esteem predicted severity (de Jong et al, 2021). The nature of the relationship between self-evaluation and eating disorder symptoms may be such that low selfesteem may predict presence, but not severity, of illness.…”
Section: Discussionmentioning
confidence: 99%
“…While past self-report studies generally show an inverse association between selfesteem and symptom severity, findings from studies using neurocognitive tasks, specifically an implicit association task which paired self-related words with positive and negative words, are mixed. For example, one study, in undergraduate women, found that negative self-evaluation negatively predicted eating disorder severity (Benas & Gibb, 2011), while a second, in patients with and without an eating disorder, found that only explicit, but not implicit, self-esteem predicted severity (de Jong et al, 2021). The nature of the relationship between self-evaluation and eating disorder symptoms may be such that low selfesteem may predict presence, but not severity, of illness.…”
Section: Discussionmentioning
confidence: 99%
“…CBM aims to modify the cognitive biases observed in depression. Due to these biases, patients preferentially attend to and remember more negative information, or interpret ambiguous situations in a more negative way than healthy individuals do (Benas and Gibb, 2009;Reid et al, 2006;Strunk and Adler, 2009). However, depressed patients also lack the positive biases or the preferred processing of positive information that is usually seen in healthy individuals (Mezulis et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is important as people with EDs often have high levels of anxiety and depression, and it is theoretically and clinically useful to identify core beliefs particularly characteristic of the ED. In terms of measurement, with the exception of Benas and Gibb [ 11 ], who used computer-based tasks to measure reaction times to specific content, most studies have assessed self-schema in EDs using self-report questionnaires or semi-structured interviews (e.g., [ 10 , 12 , 13 ]). Experimental designs, for example, Markus’s [ 1 ] “Me/Not” paradigm, have not generally been used but may provide a more objective assessment of any biased self-processing relevant to EDs.…”
Section: Introductionmentioning
confidence: 99%